2015
DOI: 10.5539/jfr.v4n5p98
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Control Measures for Bacterial Contamination in the Bovine Meat Chain: A Review on Salmonella and Pathogenic E.coli

Abstract: Salmonella and pathogenic Escherichia coli are known to be the major bacterial agents responsible for human foodborne infections attributable to meat. A review of the specialized literature was carried out to identify the risk factors for bovine meat contamination by these pathogens from the cattle farm to meat consumption. Animal stress during transport to the slaughterhouse and the duration of the lairage period were identified as the key factors influencing the faecal excretion of Salmonella and pathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 123 publications
(203 reference statements)
1
14
0
Order By: Relevance
“…As the generation time for Salmonella in optimal temperature conditions (3537°C) is known to be 25 min (Delhalle et al, 2009b), the recorded duration of carcass transportation under ambient temperature, might allow the proliferation of Salmonella cells initially present on carcasses or meat cuts. Several studies have reported bacterial proliferation during the carcass transportation stage, when the temperature was not successfully controlled (Wong et al, 2002;Niyonzima et al, 2015).…”
Section: Meat Handling Conditions In Retail Establishments Of Kigali mentioning
confidence: 99%
See 1 more Smart Citation
“…As the generation time for Salmonella in optimal temperature conditions (3537°C) is known to be 25 min (Delhalle et al, 2009b), the recorded duration of carcass transportation under ambient temperature, might allow the proliferation of Salmonella cells initially present on carcasses or meat cuts. Several studies have reported bacterial proliferation during the carcass transportation stage, when the temperature was not successfully controlled (Wong et al, 2002;Niyonzima et al, 2015).…”
Section: Meat Handling Conditions In Retail Establishments Of Kigali mentioning
confidence: 99%
“…The contamination of meat by microbial pathogens, such as Salmonella, can occur at any stage along the meat chain, from the farm to consumption (Niyonzima et al, 2015). However, the retail level, constitutes an important stage, regarding the ultimate quality and safety of meat, as it represents the last check-point where contaminated products can be identified (Wong et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Meat contamination with pathogens may originate from any point across the "farm to fork" continuum, which includes animal farming, transportation, slaughtering, processing, packaging, distribution, and meal preparation in the household environment [2,6]. The basic pillar for meat hygiene is the control measures to eliminate or reduce pathogenic or spoilage microorganisms in farms, slaughterhouses, and meat processing plants.…”
Section: Introductionmentioning
confidence: 99%
“…The actual prevalence of food-borne infections is difficult to determine, primarily because only a small percentage of incidence is officially reported. Even when cases of foodborne infections are reported, only in a limited number is the aetiology determined [3].…”
Section: Introductionmentioning
confidence: 99%